(untitled) (Philology, 2021)
emplifying it through an account of ongoing collaborative research initiated by the Department of Arabic and Semitic Studies at Sofia University St. Kliment Ohridski. Building on notions such as cultural diglossia as adopted by some Medievalists, cultural bifurcation is foregrounded as a common foundation that helps achieve a deeper understanding of three entangled key dichotomies in Arabic and Islamic studies: continuity versus change, norm versus practice, and sacred versus profane. This approach allows us to accomplish a two-fold objective—to test the suggested concept of bifurcation by discussing an interdisciplinary work in progress undertaken by a group of scholars in the fields of history and cultural studies, linguistics and literary studies under the Sofia University program on Contemporary Trends in Arabic and Islamic Studies. Hence, the analysis sheds light on internationally lesser-known aspects of the activity of Arabists and Islamicists in Bulgaria vis-à-vis some major topics in the field, combining such theorizing with approaches from history and the anthropology of science. Instead of seeking to arrive at “definitive” conclusions, this article proposes an “open-ended” reflection to encourage further research.